c.2 - "Doshi, Shambhu Lal" (New Delhi, 1971)
The present work is the revised version of the author's Doctoral dissertation entitled The changing Patterns of Bhil Life in Baswara. This study of the social change among the Bhil tribals was inspired by the personal observation of the author during his long stay in the Scheduled Area of Banswara, Rajasthan. The tradition-bound Bhil society which before the independence of India.was almost a closed system suddenly became exposed to the forces released by the Community Development movement, urbanisation, education and techonology in short, to the process of modernisation.